Case series: Computed tomography (CT) demonstrates lacrimal canal involvement in koalas (Phascolarctos cinereus) with maxillary incisor dental disease. Issue 6 (25th March 2022) - Bryce, AJ; Milne, ME; Tyrrell, D; Bodley, K
Abstract : Dental disease is common in wild and captive koalas. Effective treatments are limited and dental disease may not be recognised until it is quite severe. We describe the appearance of varying severities of dental disease on computed tomography (CT) images in a case series of six koalas. This case series demonstrates the use of CT to detect both mild and severe dental disease in koalas. The study also documents the normal CT appearance of the nasolacrimal duct in the koala. The only clinical abnormality in koalas with the mildest dental disease was ocular discharge. Computed tomography findings associated with ocular discharge were periapical lysis of first maxillary incisors, lacrimal canal remodelling and subsequent nasolacrimal duct obstruction. Dental disease should be a differential diagnosis for ocular discharge in koalas and CT examination enables visualisation of early stages of dental disease.